Assessment of The Characteristics of Nurse Scheduling in Hospital Ward - Rosly Zunaedi; Soenarnatalina Melaniani; Ahsan Ahsan (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Good scheduling arrangements are needed to prevent physical, emotional, and psychological exhaustion in nurses which will harm their performance. The aim is to see an assessment of the characteristics of nurse work scheduling in the hospital ward. This study used a descriptive survey design. The population in this study were all nurses in the ward of Lavalette Hospital - Malang. The sampling technique used was simple random sampling. Data collection using a scheduling characteristic questionnaire. Most of the respondents considered that the work scheduling criteria currently applied in the ward were in the sufficient category (80.2%). There are sub-variable coverage (309) and quality (321) less than the average value (322.08). The problems that arise in the nurse scheduling in the ward of Lavalette Hospital - Malang are the suitability of amount and distribution of nurses, quality of the schedule, an exchange between nurses, and time to prepare the schedule.